A 20-Year Experience with Tissue Expansion for Large Cervical Fascial Defects: An Algorithm Based on Different Clinical Flap Designs - Luo, Si-Si; Yang, Zhe; Ma, Ning; Li, Yang-Qun (Facial Plastic Surgery, 2023)
Over the past 20 years, we have designed various types of expanded cervical flaps for large facial defects and achieved excellent tissue matching. This study was performed to propose a treatment strategy for flap selection for the reconstruction of different facial units. The authors retrospectively reviewed the application of cervical expanded flaps for facial rehabilitation in our department between January 2003 and January 2023. The study included 122 patients with unilateral (62.3%) and bilateral (37.7%) facial deformities ranging from the zygomatic arch to the chin. The median area of the tissue defect was 15.2 × 8.5 cm2 (ranging from 6 × 4 cm2 to 27 × 12 cm2). The expansion period ranged from 61 to 175 days (mean: 86.5 days). Maximum and minimum sizes of pre-expanded cervical flaps were 30 × 13 cm2 to 7 × 5 cm2. All the flaps could be summarized into type 1, an advanced expanded cervical flap; type 2, a wing-shaped expanded cervical flap with overlapping tissue expansion; and type 3, an expanded single-lobed transposition flap rotated based on the anterior neck. Cervical flaps reliably meet the reconstructive requirements for different facial units, especially for large cutaneous defects in the clinic. The selection of these flaps can be planned preoperatively according to the location and size of the defect or lesion.
Keywords: cervical flaps; facial cutaneous defect; algorithm; reconstruction; tissue expansion technique